2021
DOI: 10.1038/s41598-021-91804-0
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicle-shuttled miRNAs as a diagnostic and prognostic biomarker and their potential roles in gallbladder cancer patients

Abstract: Circulating microRNAs (miRNAs) in serum extracellular vesicles (EVs) are a promising biomarker in cancer. We aimed to elucidate the serum EVs miRNA biomarkers to identify patients with gallbladder cancer (GBC) and to clarify their potential roles. One hundred nineteen serum EVs from GBC and non-GBC individuals were isolated by pure-EVs-yieldable size-exclusion chromatography, and then were analyzed using a comprehensive miRNAs array and RT-qPCR-based validation. The functional roles of the identified miRNAs we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 51 publications
0
31
0
Order By: Relevance
“…In particular, its upregulation has been associated with tumor growth, metastasis, and drug resistance in different types of cancer. 72 , 73 , 74 In breast cancer, exosomal miR-1246 has been used as diagnostic biomarker because of its high expression specificity.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, its upregulation has been associated with tumor growth, metastasis, and drug resistance in different types of cancer. 72 , 73 , 74 In breast cancer, exosomal miR-1246 has been used as diagnostic biomarker because of its high expression specificity.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that in the diagnosis of GBC, the sensitivity of CEA is only 11.5% and that of CA199 is 71.7% ( Wang et al., 2014 ). In another study, the AUCs of CEA and CA199 were 0.770 (sensitivity = 60%, specificity = 83.3%) and 0.729 (sensitivity = 58%, specificity = 92.6%), respectively ( Ueta et al., 2021 ). Notably, the efficacy of this five exosomal miRNAs-set in GBC diagnosis was better than that of the traditional biomarkers CA199 and CEA when the data from this study and previous studies were compared ( Ueta et al., 2021 ; Wang et al., 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…There were 20 studies written in Chinese and 7 in English. All were conducted in Asian countries, with 1 in Japan, 28 1 in India, 15 and the rest in China. The overall number of enrolled subjects was 4300, consisting of 1516 patients with GBC and 2784 non-GBC controls (286 healthy individuals and 2498 patients with related benign diseases).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Regarding study design, only the study of Bind et al 15 was designed prospectively. The majority of studies were single-centered, while six studies 10,16,23,28,29,40 adopted data from at least two centers for analysis. Table 1 shows detailed information on the main characteristics.…”
Section: Study Characteristicsmentioning
confidence: 99%